Frame-mounted tissue heart valves: technique of construction - Bartek, Ivan T. (1974)
Bartek, I. T., Holden, M. P., and Ionescu, M. I. (1974). Thorax, 29, 51-55. Frame-mounted tissue heart valves: technique of construction. The technical details for the construction and preservation of frame-mounted tissue heart valves are described. The results of clinical and experimental work which have prompted changes and improvements in valve construction are briefly discussed.